Engenharia simultânea em construtoras-incorporadoras: uma análise de maturidade - Pretti, Soraya Mattos (2013)
The civil construction sector has a great impact in Brazilian development and in the last years this important industry has been suffering with external pressures that demand products with less delivery time, less costs and higher quality. To solve these questions, approaches from other sectors have been used, as the case of concurrent engineering. Although the knowledge that concurrent engineering can be used to construction improvement, it is still unknown if companies are currently using it in their projects, how it is used and if there are means to improve this practice in their environment. Therefore, this is a qualitative research which aims to analyze these questions from the results of concurrent engineering readiness assessment of the companies. Thus, ten case studies were conducted in construction companies from Great Vitória’s region – Espírito Santo, where a new methodology of readiness assessment adapted for the local reality based on the five characteristics elements of concurrent engineering, anticipation of phase and decisions, simultaneity, multidisciplinary teams, stakeholders’ integration and quality search and insertion, was applied. The methodology was based in structured and semistrucured interviews done with the aid of forms and documentary analysis. The results find that the companies have, in general, a good readiness assessment level, classified as managed, presenting a known and characterized process, with stakeholders’ integration being their less developed factor and quality search and insertion as their most developed. This research contributes for better comprehension of the sector, as it characterizes the companies concerning their concurrent engineering readiness assessment. Likewise, it seeks to improve construction companies when it identifies the weaknesses which prevent the concurrent development of their process and proposes solutions for these problems.